Analisis Kemampuan Membaca Lancar Level 2 Siswa SD - Nadya Adila Fitri; Riza Kasmayulia; Chandra Chandra; Ari Suriani (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Fluent reading is the ability to master codes consisting of words by paying attention to the following factors: the ability to identify words automatically, the speed at which words move from one word to another, the procedures or expressions used in oral reading and accuracy. in translating the code to ensure the decoding process and understanding of the text being read. Therefore, the aim of this research is to analyze students' fluent reading abilities at level 2 in terms of reading accuracy and speed as well as fluency in reading texts with appropriate pauses, intonation and expression. The method used is a case study method through a reading test which is designed to assess the three main components of pauses, intonation and expression. The research subjects consisted of 3 2nd grade elementary school students|